DIGITALISASI PERBANKAN DAN AKSES UMKM : PELUANG DAN TANTANGAN HUKUM - Syakira Edriamarsha Firdaus; Baidhowi Baidhowi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The digitalization of banking has created opportunities for Micro, Small, and Medium Enterprises (UMKM) in Indonesia to access financing more easily and efficiently. Through digital banking services, the loan application and disbursement processes have become faster, thereby enhancing financial inclusion for UMKM. However, the implementation of this digitalization also faces various legal challenges, such as personal data protection, the security of electronic transactions, and regulations that are not yet fully adaptive to technological developments. Therefore, a comprehensive and flexible legal framework is needed to support the synergy between banking digitalization and UMKM, to ensure the optimal use of technology and legal protection for all parties involved.